The successful of UMP reading circle program - Nursyaheedah, Muhammad Isa (Pejabat Naib Canselor, 2016)
Reading Circle Program (RCP) for Gambang Campus was successfully held at Astaka Hall, Universiti Malaysia Pahang on April, 27 2016.